A New Paradigm of Islamic Religious Education In Facing Globalization - Nur Faidatul Hasanah; Aminatuz Zahroh (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Globalization has brought about significant changes in social, cultural, and educational aspects, impacting the implementation of Islamic Religious Education (PAI). This study aims to analyze the new paradigm of Islamic Religious Education in facing the challenges of globalization through an integrative and transformative approach. The research method used is library research by analyzing various scientific sources in the form of books, journals, and documents related to Islamic education and globalization. The results show that Islamic Religious Education needs to transform from a conventional approach to learning that integrates Islamic values ​​with developments in science and technology. This new paradigm emphasizes character building, critical thinking skills, creativity, digital literacy, and the development of student competencies so they can adapt to changing times without abandoning Islamic values. The main challenges identified include teacher resistance to changes in learning methods, limited educational facilities and resources, especially in remote areas, and parents' low understanding of the new educational paradigm. Furthermore, the assessment system, which is still oriented towards memorization, poses a challenge to the implementation of holistic learning. Efforts to address these problems include ongoing teacher training and professional development, the provision of equitable educational facilities and infrastructure, the development of a technology-based contextual curriculum, and increased collaboration between schools, the government, parents, and the community through intensive outreach and education. Thus, the new paradigm of Islamic Religious Education is expected to create a generation that is faithful, virtuous, adaptive, and able to compete in the era of globalization.